An overview of Sirtuins as potential therapeutic target: Structure, function and modulators - Wang, Yijie; He, Jun; Liao, Mengya; Hu, Mingxing; Li, Wenzhen; Ouyang, Hongling; Wang, Xin; Ye, Tinghong; Zhang, Yiwen; Ouyang, Liang (European journal of medicinal chemistry, 2019)
Sirtuin (Yeast Silent Information RegulatorsⅡ, Sir2) was first discovered in the 1970s. Because of its function by removing acetylated groups from histones in the presence of nicotinamide adenine dinucleotide (NAD+), waves of research have assessed the potential of Sirtuin as a therapeutic target. The Sirtuin family, which is widely distributed throughout the nature, has been divided into seven human isoforms (Sirt1-Sirt7). They are thought to be closely related to some aging diseases such as cardiovascular disorders, neurodegeneration, and tumors. Herein, we present a comprehensive review of the structure, function and modulators of Sirtuins, which is expected to be beneficial to relevant studies. [Display omitted] •The roles of Sirtuins are thoroughly discussed.•The functions of Sirtuins are outlined.•An overview for the modulators of Sirtuins is introduced in detail.